1981
DOI: 10.3133/b1494
|View full text |Cite
|
Sign up to set email alerts
|

Mineral resources of the Cranberry Wilderness study area, Webster and Pocahontas counties, West Virginia, with sections on peat resources, oil and gas potential, and geochemical survey

Abstract: No. 3(?) coal bed __________________ 18 Pocahontas No. 3(?) rider coal bed _______________-Little Fire Creek(?) coal bed __________________-Fire Creek(?) coal bed _______________________ 32 Beckiey(?) coal bed ________________________.. Little Raleigh(?) coal bed _____________________ Little Raleigh(?) rider coal bed _________________ 37 Sewell coal bed ____________________________ Hughes Ferry(?) coal bed ___________________._ Peat resources, by C. C. Cameron and A. E. Grosz _________ 40 Shale and clay ______… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The open peatlands of CGBA (Figure 1d) have been shrinking for at least a century due to woody encroachment associated with water table drop [19,41,47]. Stine et al (2011) suggested that beavers have been integral to the formation and maintenance of Sphagnumdominated peatland conditions at Cranberry Glades [38].…”
Section: Study Sitementioning
confidence: 99%
“…The open peatlands of CGBA (Figure 1d) have been shrinking for at least a century due to woody encroachment associated with water table drop [19,41,47]. Stine et al (2011) suggested that beavers have been integral to the formation and maintenance of Sphagnumdominated peatland conditions at Cranberry Glades [38].…”
Section: Study Sitementioning
confidence: 99%